Meta-analysis of the relationship between university students' anxiety and academic performance during the coronavirus disease 2019 pandemic - Tang, Yuxi; He, Weiguang (Frontiers in Psychology, 2023)
Introduction The COVID-19 pandemic has had a profound impact on the mental health and academic performance of university students worldwide. Anxiety is one of the most commonly reported mental health issues among this population, but its relationship with academic performance during the pandemic has not been fully explored. Methods A meta-analysis was conducted following the PRISMA-P guidelines to synthesize existing research on the relationship between anxiety and academic performance in university students during the COVID-19 pandemic. Four databases were searched (PsycINFO, Web of Science, PubMed, and Scopus) for articles published between December 2019 and June 2022, and studies from five different countries were included in the analysis. A heterogeneity test was performed, and a fixed-effects model was used to calculate the main results. Results The meta-analysis revealed a negative correlation between university students' anxiety and academic performance (r = −0.211, k = 5, N = 1,205). Subgroup analysis found no significant regulatory effects for the year of publication, country development level, student type, or anxiety type. The results suggest that negative emotions induced by the pandemic are the most significant factor linking anxiety to poor academic performance. Discussion During pandemics with severe global consequences, such as COVID-19, interventions against and for the prevention of university students' negative emotions are important ways to improve university students' mental health and academic achievement.